Urgensi Reformasi Hukum Kepailitan dalam Memitigasi Risiko Sistemik terhadap Stabilitas Makroekonomi - Sudhana, Harry; Muhammad Ruhunussa; Raden Giri; Raineldis Bero; Yusfika Ely Nur Afifah; Edi Mulyadi (Draf Solusi Indonesia, 2025)
This study examines the urgency of bankruptcy law reform within the framework of mitigating systemic risks that threaten macroeconomic stability. As theoretical research, this article analyzes the correlation between the efficiency of insolvency regimes and macroeconomic variables such as investment, banking sector health, and resource allocation. The findings indicate that a rigid bankruptcy law, which is merely oriented toward formal-legalistic aspects, can trigger the